ANALYSIS OF MARKETING CAPABILITY AND MARKET AMBIDEXTROUS ON PRODUCT INNOVATION RESULTS: INTEGRATION OF DYNAMICS BETWEEN INTERNAL AND EXTERNAL APPROACHES - Zaenal Aripin; Faisal Matriadi; Lili Adi Wibowo (PT. Kreatif Indonesia Satu, 2024)
The dynamic integration between internal and external approaches plays an important role in improving a company's marketing capabilities in producing successful product innovations. In this context, strategies and best practices such as in-depth market research, cross-functional collaboration, use of technology and data analytics, formation of strategic partnerships, and a strong innovation culture are key. In-depth market research helps companies understand customer needs and preferences as well as emerging market trends, while cross-functional collaboration allows them to maximize internal knowledge and expertise. The use of technology and data analytics helps companies collect and analyze market data more effectively, while the formation of strategic partnerships allows them to access additional resources and knowledge. Finally, a strong innovation culture is an important foundation for creating an environment that supports sustainable product innovation. By implementing these strategies, companies can improve their ability to produce relevant and sustainable product innovations, thereby remaining competitive in an increasingly complex market.